Analisis Stress Kerja Karyawan: Studi Kasus Pada PT X - Ruth Damayanti Simanjuntak; Christian Wirandendi Wolor; Eka Dwi Utari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aims to analyze employee work stress at PT X. The objectives of this study include understanding the factors that cause employee work stress at PT X, knowing the strategies used by PT X in overcoming work stress, and the company's response to employee work stress that occurs at PT X. The research method used is descriptive analysis with a qualitative approach. The background of this research is based on excessive workload in the work environment, decreased motivation caused by a lack of attention from the company to workers. The results of this study show that high levels of stress among PT X employees significantly affect employee performance. Employees often feel frustrated to the point of forcing themselves to complete work quickly. As a result, employees are exposed to work stress and performance productivity decreases. To overcome this problem. PT X has implemented workload mapping strategies, appreciation in the form of compensation, and recruitment of new employees. The implementation of this strategy has shown positive results in improving employee productivity and performance efficiency. This study concludes that high work stress has certain consequences on employee performance. Recommendations include stress management programs, periodic performance effectiveness evaluations, and further studies that explore the relationship of job stress with other variables, such as individualism and leadership. The findings are expected to contribute to the development of more effective human resource management strategies in modern work environments.